The effectiveness of materials and the activities that teachers use inside and outside the classroom to help students to develop critical thinking in Readings and Conversation I, semester II, 2013. - Flores Iraheta, Ana Ruth; García Martínez, Ena Rubidia; Quijada Monterrosa, Gabriela; Gómez Alegría, Ana Grace; Ayala Edgar Nicolas (San Salvador, El Salvador : 2014, 2014)
This paper reports on the findings of a study conducted to investigate the effect of the materials and the activities used by teachers in the subject of Readings and Conversations I, over students’ development of critical thinking. The study found that during this course, it is being applied a new teaching methodology that facilitates the enhancement of Critical Thinking not only inside but also outside the classroom. However, as the team could conclude, there are negative responses of students to such methodology, due to their position towards learning. These findings will help teachers to reinforce motivation through the use of their materials design in terms of helping students to develop reading habits and keeping on mind that: “If the focus is on learning, students should be given the freedom (and responsibility) to explore contents, analyze resources, and apply information. Unfortunately, students are not typically taught to think or learn independently, and they rarely “pick up” these skills on their own (Ladsman & Gorski, 2007; Lundquist, 1999; Rippen, Booth, Bowie, & Jordan, 2002).” This will lead to a more complete Critical Thinking building and to a better learning competence and production in students’ academic and professional career.
anexos y glosario.
Texto en Español e Ingles
Keywords: Inglés -- Enseñanza